Taiwanese and Sri Lankan students' dimensions and discourses of professionalism. Issue 7 (25th April 2017) - Monrouxe, Lynn V; Chandratilake, Madawa; Gosselin, Katherine; Rees, Charlotte E; Ho, Ming‐Jung
Abstract : Context: The definition of medical professionalism poses a challenge to global medical educators. This is especially pronounced in settings where professionalism frameworks developed in the west are transferred into different cultures. Building upon our previous study across Western contexts, we examine Taiwanese and Sri Lankan medical students' conceptualisations of professionalism in terms of what professionalism comprises (i.e. dimensions) and how it is linguistically framed (i.e. discourses). Methods: A qualitative group interview study was undertaken comprising 26 group interviews with 135 participants from one Taiwanese ( n = 64; Years 4–7) and one Sri Lankan medical school ( n = 71; Years 2–5). Through thematic framework analysis we examined the data for explicit dimensions of professionalism. Through discourse analysis we identified how participants constructed professionalism linguistically (discourses). Results: Thirteen common dimensions across Taiwanese and Sri Lankan talk were identified, with the dimensions (contextual, integration and internalised self) being identified only in Sri Lankan data. Professionalism as knowledge and patient‐centredness were dominant dimensions in Taiwan; in Sri Lanka, attributes of the individual and rules were dominant dimensions. Participants in both countries used four types of discourses previously identified in the literature. Individual and interpersonal discourses were dominant in Taiwanese talk; the collective discourse was dominant in Sri Lankan talk. Findings were compared with our previous data collected in Western contexts. Conclusions: Despite some overlap in the dimensions and discourses identified across both this and Western studies, Taiwanese and Sri Lankan students' dominant dimensions and discourses were distinct. We therefore encourage global medical educators to look beyond a one‐size‐fits‐all approach to professionalism, and to recognise the significance of context and culture in conceptualisations of professionalism.